Effects of an educational intervention regarding fair play on sports team coaches - Sampol, P. P.; Bermejo Diaz, J. M.; Borràs Rotger, P. A.; Ponseti Verdaguer, F. J. (Journal of Human Sport & Exercise, 2020)
The objective of this study was to analyse the effectiveness of an intervention program aimed at coaches to evaluate their attitude in favour of fair play in sports, aspects such as fun, the need to win, antisocial behaviours (hard play, gamesmanship, and cheating) in young athletes of the Balearic Islands. The sample includes soccer, basketball and volleyball teams with a total of 1097 participants (854 boys and 243 girls) with an average age of 12.50 years and an age range between 10-16 years of the categories novice, juvenile and cadet of the 2016-2017 season, to which the adapted Spanish version of the Sport Deception Disposition Questionnaire (CDED) and the Fair Play Attitude Scale (EAF) was administered at two different times (pretest-posttest). The results show that young athletes value sport positively as fun at both moments of the season. The intervention program works, although not significantly, in the reduction of antisocial behaviours of victory, gamesmanship and cheating. With regard to sex, men obtain higher results in the so-called antisocial behaviours of sport in the first phase of the program, while women obtain greater results in pro-social sports behaviours. In a novel way, women obtain higher scores in hard play and cheating in the second phase of the program.